1999
DOI: 10.1007/s003470050372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of special effect soft lenses on visual function

Abstract: The tested special-effect contact lenses are associated with a reduction of many visual functions, including visual acuity and contrast sensitivity. This may interfere in some wearers with the ability to drive a car.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
15
2
2
Order By: Relevance
“…Moreover, a significant correlation was observed between declines in contrast sensitivity in a photopic condition and increases in higher-order aberrations in this study. So far, there have been two studies that showed reduction of contrast sensitivity in a photopic condition after the use of tinted contact lenses [1,5]. However, the reason why contrast sensitivity was compromised by wearing the lenses was not mentioned in those articles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, a significant correlation was observed between declines in contrast sensitivity in a photopic condition and increases in higher-order aberrations in this study. So far, there have been two studies that showed reduction of contrast sensitivity in a photopic condition after the use of tinted contact lenses [1,5]. However, the reason why contrast sensitivity was compromised by wearing the lenses was not mentioned in those articles.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, we sometimes observe that tinted soft contact lens wearers report blurred vision or night vision disturbance even though visual acuity measured with high-contrast acuity chart is sufficiently good. Ozkagnici et al [5] showed that contrast sensitivity was significantly decreased in opaquely tinted soft contact lens wearers, and Spraul et al [1] demonstrated that tinted contact lenses significantly reduced contrast sensitivity in both photopic and scotopic conditions. However, little is known about the mechanism of reducing contrast sensitivity following the wearing of tinted contact lenses.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[12,13] 하지만 써클렌즈의 착용 연령이 낮아지고 있으며, 젊은 연령층의 경우는 저가 써클렌즈를 착용하는 빈도가 많아 [14] 이로 인해 부정난시 가 발생하는 써클렌즈 신드롬, [15] 동공을 가려서 생기는 시 력저하 [16] 등의 부작용이 보고되고 있다. 또한 써클렌즈의 부작용과 착색제와 착색공법에 의한 저산소증 및 각막의 손상 등의 연관성에 대해 보고된 바 있다.…”
Section: 서 론unclassified